Inflammatory pseudotumour: A rare tumor of lung. (December 2018) - Marwah, Nisha; Bhutani, Namita; Dahiya, Sakshi; Sen, Rajeev
Abstract: Inflammatory pseudotumours of the lungs have rarely been reported. These have been described as a benign entity of unknown origin and are often locally invasive requiring extensive pulmonary resection. Complete resection is the key to prevent recurrence and the prognosis is excellent following surgery. We describe a patient with inflammatory pseudotumour of the lung. He was a middle aged man who presented with haemotysis and the chest X-ray and computerized tomography were indicative of a nonbenign lesion in the right upper lobe. Excision biopsy confirmed the diagnosis of inflammatory myofibroblastic pseudotumour of the lung. This is a rare inflammatory nonneoplastic condition commonly affecting children and young adults. Highlights: The inflammatory pseudotumor of the lung is a rare entity. Surgical excision is usually indicated to reach a firm diagnosis and cure. As preoperative investigation is not diagnostic, excision of the mass is imperative in order to exclude malignancy. Despite being a benign lesion, its potential for recurrence and local invasion requires complete surgical resection. Complete resection, when possible, is safe and leads to excellent survival and remains the key to prevent recurrence.